Social connections and incentives in the workplace: evidence from personnel data - Oriana Bandiera; Iwan Barankay; Imran Rasul (Institute for the Study of Labor (IZA), 2008)
We present evidence on the effect of social connections between workers and managers on productivity in the workplace. To evaluate whether the existence of social connections is beneficial to the firm's overall performance, we explore how the effects of social connections vary with the strength of managerial incentives and worker's ability. To do so, we combine panel data on individual worker's productivity from personnel records with a natural field experiment in which we engineered an exogenous change in managerial incentives, from fixed wages, to bonuses based on the average productivity of the workers managed. We find that when managers are paid fixed wages, they favor workers to whom they are socially connected irrespective of the worker's ability, but when they are paid performance bonuses, they target their effort towards high ability workers irrespective of whether they are socially connected to them or not. Although social connections increase the performance of connected workers, we find that favoring connected workers is detrimental for the firm's overall performance.
urn:nbn:de:101:1-20090119137
Keywords: J33; M52; M54; 330; Favoritism; managerial incentives; natural field experiment; Arbeitsbeziehungen; Soziale Beziehungen; Vergütungssystem; Führungskräfte; Patronage; Arbeitsproduktivität; Unternehmensentwicklung; USA